Pengaruh Partisipasi Komite Sekolah Terhadap Efektivitas Pengambilan Keputusan Strategis Pada Sekolah Dasar Negeri Di Kabupaten Pasuruan - Nahdiah Nur Fauziah; Erma Fatmawati; Imron Fauzi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Decentralization of education requires community involvement in school management through school committees as a form of school-based management. However, the level of school committee participation in strategic decision-making still varies, so it needs to be studied empirically. This study aims to analyze the influence of school committee participation on strategic decision-making in public elementary schools in the era of education decentralization. The research approach used a quantitative method with an explanatory design. The research sample consisted of 30 respondents, including 15 school principals and 15 committee members from 15 public elementary schools in Pasuruan Regency. Data were collected through a Likert scale questionnaire and analyzed using simple linear regression with the help of SPSS version 26. The results showed a positive and significant influence between school committee participation and strategic decisionmaking (R = 0.712; R² = 0.507; Sig. = 0.000). This means that 50.7% of the variation in strategic decision effectiveness is explained by the level of school committee participation. The higher the committee's involvement in planning, implementing, and evaluating school programs, the more effective the strategic decision-making process will be. These findings emphasize the importance of applying the principles of good governance and school-based management in strengthening participatory, transparent, and accountable education governance.